Risk factors for high risk Human Papillomavirus (HR-HPV) infection among unscreened African women aged thirty-five to sixty-five years - De Souza, Michelle (Department of Medicine, 2024)
Introduction: Persistent infection with high risk types of Human Papillomavirus (HRHPV) is a known necessary cause of cervical cancer which is the second most common cancer in women around the world. Genital HPV infection is one of the commonest sexually transmitted infections in the world. This study was designed to evaluate the prevalence of HR-HPV in previously unscreened African women aged thirty-five to sixty-five years and to determine the socio-demographic, behavioural, contraceptive use and biological risk factors for HR-HPV infection among these women. Methods: This was a cross-sectional analytic study design using data derived from a randomized control trial (SAT study) evaluating screen and treat modalities, which was located in an area called Khayelitsha in the Western Cape. At enrolment, all women underwent a clinical examination, completed a questionnaire on demographic characteristics and sexual behaviors, and provided blood samples for HIV testing. Samples for Neisseria gonhorreae and Chlamydia trachomatis were collected using endocervical cone-brushes and tested using the Hybrid Capture GC/CT DNA Assay Endocervical cone-brush samples were tested for Human Papilloma Virus (HPV) DNA using the Hybrid Capture II HPV DNA Assay. Wet mount exams were performed on-site during the clinical examination by trained study nurses to identify Trichomonas vagina/is and Bacterial vaginosis was assessed during the clinical examination using Amsel criteria. Data from the enrollment visit was analyzed for 6645 participants and a multiple logistic regression analysis was performed to evaluate the risk factors for HR-HPV infection. - 14 - Results: In total, 6645 participants were included in the analysis. Of these women, 1416 (21.3%, 95% confidence interval (CI); 20.3; 22.3) tested positive for HR-HPV infection. The multivariate logistic regression analysis showed that a positive Human immunodeficiency virus (HIV) status (odds ratio (OR); 4.08, 95% CI; 3.47; 4.80), previous sterilization (OR; 0.72, 95% CI; 0.61; 0.85), current use of condoms (OR; 2.15, 95% CI; 1.22; 3.80), current use of Depot medroxyprogesterone acetate (DMPA) (OR; .. 1.37, 95% CI; 1.13; 1.65), current use ofNorethindrone enanthate (Net-EN) (OR; 1.39, 95% CI; 1.02; 1.88), currently married (OR; 0.71, 95% CI; 0.62; 0.81), mean number of live births (OR; 1.10, 95% CI; 1.06; 1.14), mean age in years (OR; 0.99, 95% CI; 0.98; 0.997) and currently employed (OR; 0.86, 95% CI; 0.74; 0.99) were significant in a model predicting the odds of infection with HR-HPV when adjusted for other sociodemographic, behavioural and biological variables and use of contraception. Conclusions: In conclusion, this study shows that there is a very high prevalence of HRHPV infection in African women aged thirty-five to sixty-five years living in Khayelitsha. The overwhelming association between HIV infection and HR-HPV infection in this study has very important clinical and policy implications in the communities where HIV infection, Acquired immunodeficiency disease syndrome (AIDS) and cervical cancer are major health problems. This study also adds onto the knowledge of risk factors for HR-HPV infection, but introduces the possibility of longacting injectable progesterones (LAIP) having a significant effect on the prevalence of HR-HPV infection and highlights the need for further research into the risks ofHR-HPV infection